The Impact of Collaboration of Police and Community in Barangay Holy Spirit Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
AbstractCollaboration is the process of coming together and cooperating to address a challengingissue. The collaboration of the Philippine National Police and the Community is a powerful toolfor fostering social stability and peace. The main goals of the police are to safeguard society,provide for the citizens' freedom, justice, and security, and to prevent and deter criminalactivity within society. Although it can be challenging for the police to effectively battle criminalactivity in some complex cases, there are some situations in which they must work with thecommunity to guarantee everyone is safe.Developed community relations for public cooperation and participatory leadership andsocialization in the community.On the basis of such findings, recommendations were made that conduct regular jointmeetings and planning sessions to discuss and address community safety concerns. This canhelp ensure that the police and barangay officials are aligned on their priorities and strategies.
Keywords: Criminology